Effectiveness of Hands-on Learning Activities in Improving the Performance of Kindergarten Learners - Siabo, Kelly Jam G.; Resuento, Rhea G. (International Journal of Membrane Science and Technology, 2023)
This study determined the effectiveness of hands on activities in improving the performance of kindergarten in two selected schools in the Division of Talisay City and Division of Cebu City for the school year 2022-2023 as basis for a proposed action plan. This study determined the effectiveness of hands on activities in improving the performance of kindergarten in two selected schools in the Division of Talisay City and Division of Cebu City for the school year 2022-2023 as basis for a proposed action plan. Through a descriptive-comparative study, survey questionnaires were given to 209 parents and teachers as the respondents across the said two schools and the data obtained were analyzed using descriptive and correlational statistics. Results revealed that parents and teacher’s perception in the effectiveness of hands on activities in improving the performance of kindergarten learners are very effective. It was also evident that incorporating hands-on learning into the classroom or into the home is an easy way to show children exactly how they are learning can be used in the real world. There were observed a significant relationship between parents and teacher’s perception in the effectiveness of hands on activities in improving the performance of Kindergarten learners. In conclusion, it’s important to note especially to the parents and teachers that when people hear the word “creativity,” their minds often go immediately to subjects like art and music. While these are of course important classes for children, and should play a role in child’s education. Parents and teachers should be involved in order to manifest learning using the effectivity of hands-on activity. Action plan was formulated to provide help and support to parents and the school in general.